2012
DOI: 10.5402/2012/762340
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's Gangrene: Conventional Dressings versus Dressings with Dakin's Solution

Abstract: Purpose. Fournier's gangrene is a fulminant and destructive inflammation of the scrotum, penis, and perineum. The objective of this study was to compare 2 different approaches to wound management after aggressive surgical debridement. Methods. Data from 14 patients with Fournier's gangrene were retrospectively collected (2005–2011). Once the patients were stabilized following surgery, they were treated with either daily antiseptic (povidone iodine) dressings (group I, n = 6) or dressings with dakin's solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…Additionally, this concentration had been proven to be not only bactericidal but also nontoxic to host tissues. In a study by Altunoluk et al [44] it was shown that Dakin solution dressing reduced hospital stay morbidity and mortality. Application is justified when hydrogen peroxide is used in the correct circumstances, but precautions should be taken when used in closed spaces or under pressure, where liberated oxygen cannot escape, and dangerous side effects are described as blood oxygen embolism.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Additionally, this concentration had been proven to be not only bactericidal but also nontoxic to host tissues. In a study by Altunoluk et al [44] it was shown that Dakin solution dressing reduced hospital stay morbidity and mortality. Application is justified when hydrogen peroxide is used in the correct circumstances, but precautions should be taken when used in closed spaces or under pressure, where liberated oxygen cannot escape, and dangerous side effects are described as blood oxygen embolism.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Some entities have strongly discouraged its use in wound care, especially because of its presumed cytotoxicity to healthy tissues, an observation mostly seen in laboratorial investigations. Nevertheless, this debatable yet relevant concern has not been definitely substantiated by in vivo studies and has especially not been significantly observed in real‐world clinical practice, where several successful reports regarding the medical use of DS have been published . Extremely inflammatory and infected human wounds create a dynamic complex environment that is difficult to replicate with precision in the laboratory, which at least partially justifies the disagreement in the laboratory and real‐world clinical practice with regard to observed cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this debatable yet relevant concern has not been definitely substantiated by in vivo studies 17 and has especially not been significantly observed in real-world clinical practice, where several successful reports regarding the medical use of DS have been published. [8][9][10][11][12] Extremely inflammatory and infected human wounds create a dynamic complex environment that is difficult to replicate with precision in the laboratory, which at least partially justifies the disagreement in the laboratory and real-world clinical practice with regard to observed cytotoxicity. For example, open wounds contain a myriad of components (serum, pus, necrotic debris) that probably mitigate the potential toxicity of DS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations